2008
DOI: 10.1111/j.1349-7006.2008.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive tumor features accompany epithelial–mesenchymal transition induced in mitochondrial DNA–depleted cells

Abstract: The growth of LNCaP, a human prostate adenocarcinoma cell line, and MCF-7, a human breast adenocarcinoma cell line, is initially hormone dependent. We previously demonstrated that LNr0-8 and MCFr0, derived from LNCaP and MCF-7 by depleting mitochondrial DNA (mtDNA), exhibited hormone-independent growth that led to progressed phenotypes. Here, we demonstrate that LNr0-8 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…Transfer of mutated mtDNA from highly metastatic cell lines is sufficient to initiate a metastatic phenotype in non-metastatic cell lines by promoting mitochondrial ROS production (Ishikawa et al, 2008). Moreover, mtDNA depletion in MCF-7 cells induces an EMT programme (Naito et al, 2008). Our results show that PNC1, by regulating the mitochondrial ROS production, has the potential to regulate initiation of an ROS-dependent EMT programme in tumour cells.…”
Section: Pnc1 Regulates Mitochondrial Function and Emtmentioning
confidence: 72%
“…Transfer of mutated mtDNA from highly metastatic cell lines is sufficient to initiate a metastatic phenotype in non-metastatic cell lines by promoting mitochondrial ROS production (Ishikawa et al, 2008). Moreover, mtDNA depletion in MCF-7 cells induces an EMT programme (Naito et al, 2008). Our results show that PNC1, by regulating the mitochondrial ROS production, has the potential to regulate initiation of an ROS-dependent EMT programme in tumour cells.…”
Section: Pnc1 Regulates Mitochondrial Function and Emtmentioning
confidence: 72%
“…To approach this question, we have silenced hnRNP A2/B1 in a panel of lung cancer cell lines that present a different EMT phenotype: mesenchymal H1703, intermediate A549, and epithelial H358 (30). EMT differentiation has been reported to affect migration and proliferation (28,29), and EMT induction has been observed as part of a response to mitochondrial stress (27).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that depletion of mitochondrial DNA in cancer cells promotes epithelial-mesenchymal transition (EMT; ref. 27). Moreover, it has also been proposed that changes in morphology, invasion, and metastasis potential could be the result of EMT (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…22 The knock-out of the mtDNA (mtDNA-KO) from LNCaP and MCF-7 was demonstrated in the creation of the LNr0-8 and MCFr0 cell lines, respectively. 9,10 To confirm that experimental observations that follow the loss of the mitochondrial genome content are not of consequence to an incidental mutation to the nuclear genome induced by ethidium bromide treatment, the mitochondrial genome was reconstituted to the mtDNA-KO cell lines (LNr0-8 and MCFr0) in the creation of the mtDNA-knock in (mtDNA-KI) cells lines, denoted as LNCyb and MCFCyb.…”
Section: Resultsmentioning
confidence: 99%
“…We showed following observations to demonstrate the mechanisms involved in the induction of advanced phenotype of PCa by the reduction of mitochondrial genome content. Reduction of mtDNA content shifted (1) androgen-dependent PCa cells to an androgenindependent phenotype in vitro and in vivo 9 and induced (2) epithelial-to-mesenchymal transition changes that may lead to PCa progression, 10 (3) hypermethylation of CpG islands of the putative tumor suppressor genes 11 and (4) abnormal activation of NF-kB, 12 AP-1, 12 AKT, 13 ERK 10 and JNK 10 that may lead to aggressive phenotype in PCa progression.…”
Section: Subject Category: Cancermentioning
confidence: 99%